The Effect of The Mediation Role of Value Co-Creation on Patient Participation and Customer Relationship Management (CRM) on Patient Loyalty - Ratri, Ayuningtyas Dewi; Aini, Qurratul (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2024)
Patient loyalty has become a critical success factor for healthcare institutions in the evolving healthcare landscape. The hospital seeks to differentiate itself by emphasizing patient-centered care, robust CRM systems, and the value of co-creation. This research analyzed the mediation of value co-creation on patient participation and customer relationship management toward patients' loyalty at the Obstetrics and Gynaecology Polyclinic of Islamic Hospital of Hj. Siti Muniroh Tasikmalaya. This quantitative methodology used a cross-sectional survey and primary data from the questionnaire. The sample size was 271 patients. The sampling technique used purposive sampling, a sampling technique with the criteria. The analysis technique was Partial Least Square (PLS). The result indicated that the patient’s participation and customer relationship management toward loyalty had a mediation effect from the value co-creation variable. Patient participation and CRM affect value co-creation in outpatients at the Obstetrics and Gynaecology Polyclinic of the Islamic Hospital of Tasikmalaya, both partially and simultaneously. The hospital should actively engage patients in co-creating healthcare experiences by involving them in treatment decisions, personalized care plans, and feedback loops. Then, the implication of this research was to enhance value co-creation, which could increase patient satisfaction, leading to higher loyalty and more effective CRM efforts.